2020
DOI: 10.3329/medtoday.v32i2.48821
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility Pattern of Klebsiella Pneumoniae Isolated from Various Clinical Specimens in a Tertiary Care Hospital in Bangladesh

Abstract: Introduction:Klebsiella pneumoniae are common causative agents of various infections and are of great concern for developing resistance against commonly prescribed antibiotics. This study gives an account of isolation of K. pneumoniae from various clinical specimens and their antimicrobial susceptibility, in a tertiary care hospital of Bangladesh. Materials and Methods: Various clinical specimens like urine, wound swab, sputum, blood and endotracheal aspirates were collected and processed for isolation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Result of this study revealed that K. pneumoniae had higher resistance to ciprofloxacin (82%). In consistent with this finding, another study [30] observed that K. pneumoniae bacterial types are generally insensitive to ciprofloxacin (88%). High resistance rate to imipenem and ciprofloxacin in the present study might be due to uncontrolled consumption of these antibiotics in Iraq.…”
Section: Discussionsupporting
confidence: 70%
“…Result of this study revealed that K. pneumoniae had higher resistance to ciprofloxacin (82%). In consistent with this finding, another study [30] observed that K. pneumoniae bacterial types are generally insensitive to ciprofloxacin (88%). High resistance rate to imipenem and ciprofloxacin in the present study might be due to uncontrolled consumption of these antibiotics in Iraq.…”
Section: Discussionsupporting
confidence: 70%
“…The isolation rate of K. pneumoniae from total processed samples came out to be 5.24% (248/4724) and from 1336 growth positive samples the isolation rate of K. pneumoniae came out to be18.56% (248/1336). The prevalence correlates to great extent with the studies by Nirwati et al, Gill et al, Farkhanda et al, Sodhi et al, Sonia et al and Odari et al who reported prevalence to be 17.36%, 22.43%, 15.18%, 21.23%, 23.73% and 15.7% respectively [17][18][19][20][21][22]. However, Pyakurel et al reported prevalence 31.4% which is higher than the present study 23.…”
supporting
confidence: 74%
“…Lev et al (2018) reported that the overall prevalence of K. pneumoniae in hospital-acquired infections in Moscow, Russia, was 16.66%, of which; 30% were from urine and 3% from blood samples. Out of 500 samples, 75 K. pneumoniae (23.73%) were isolated from urine (18.67%), blood (8%) and other samples in Bangladesh (Sonia et al, 2020). In Indonesia, 167 (17.36%) K. pneumoniae isolates were recovered from 962 clinical specimens, of which 12 (7.19%) were from urine and 18 (10.78) from blood (Nirwati et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Out of 500 samples, 75 K . pneumoniae (23.73%) were isolated from urine (18.67%), blood (8%) and other samples in Bangladesh (Sonia et al, 2020). In Indonesia, 167 (17.36%) K .…”
Section: Discussionmentioning
confidence: 99%